Effects of training resumption on conduit arterial diameter in elite rowers - Naylor, L. H.; O'Driscoll, G.; Fitzsimons, M.; Arnolda, L. F.; Green, D. J. (Medicine & Science in Sports & Exercise, 2006)
Background: Exercise training is a known stimulus for arteriogenesis, but it is unclear whether elite athletes, who exhibit increased conduit vessel diameter at rest, experience further structural vascular adaptations as a result of intense exercise training.